Relational Autonomy in Spinoza. Freedom and Joint Action - Aguilar, Claudia (2022)
Over the last years, some of Spinoza studies have shifted to a consideration of the relational character of his ethics by focusing on the notion of autonomy. This concept is foreign to Spinoza's vocabulary. Therefore, I will attempt to explain what Spinozan relational autonomy is and its connection with the most important ethical concept in his philosophy: freedom. Following considerations about Spinozan freedom, I claim that it entails a relational character and that, for this reason, it is equal to relational autonomy. We are free when our joint action is based on adequate ideas of what we have in common with others.